2022
DOI: 10.1039/d2tc01244h
|View full text |Cite
|
Sign up to set email alerts
|

Macromatrices for nanoscale particles

Abstract: This review presents three main categories of macromatrices explored so far for NP encapsulating, including ionic and organic macrocrystals and polymeric matrices. The preparation methods and the recent progress for each category have been discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 148 publications
0
1
0
Order By: Relevance
“…Such a high value makes it comparable to the levels that inorganic, toxic quantum dots or some uorescent polymers provide. 36,37 In the literature, Hidalgo et al 38 reported the QYs of norharman, harmane, harmalol, and harmol, which are the chemical compounds in P. harmala extract, as 16%, 17%, 39%, and 49%, respectively. These values were signicantly lower than our QY results.…”
Section: Resultsmentioning
confidence: 99%
“…Such a high value makes it comparable to the levels that inorganic, toxic quantum dots or some uorescent polymers provide. 36,37 In the literature, Hidalgo et al 38 reported the QYs of norharman, harmane, harmalol, and harmol, which are the chemical compounds in P. harmala extract, as 16%, 17%, 39%, and 49%, respectively. These values were signicantly lower than our QY results.…”
Section: Resultsmentioning
confidence: 99%